Analisis Proksimat Berbagai Jenis Kacang-kacangan yang Tumbuh di Pulau Timor-NTT - Dhanang Puspita; Sarlina Palimbong; Nathania Liantari Pratamaningtyas; Kristiawan Prasetyo Agung Nugroho (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Almost throughout Indonesia, bean/legume plants can grow well. In the province of East Nusa Tenggara,Timor island there are many local beans that grow wild or cultivated. Local beans in the island of Timor,mostly processed into jagung bose (traditional meal made from corn) . Not much variety of food types basedon local beans. This study aims to identify the nutritional value of local beans in the island of Timor. Themethod used is by measuring the content of proteins, carbohydrates and fats. From the analysis of theresults obtained, the beans with the highest protein are arbila merah (18.55%), the highest carbohydratesare arbila biji besar (76.16%), and the highest fat are arbila biji loreng (1.85%). The results of this analyzecould be a recommendation in the processing of beans-based food to increase the added value andcommunity nutrition.